Blackbeard : a notorious pirate in the Caribbean - Cooke, Tim, 1961- (Cooke, Tim, 1961- Wanted! Famous outlaws., 2016)
"Edward Teach, otherwise known as the pirate Blackbeard, was a terror of the seas in the 1700s. Merchant ships had little choice but to surrender to his 40-cannon Queen Anne's Revenge. At one point, Teach accepted a pardon but couldn't retire from piracy for good. This adventurous volume takes readers into the background of the famous figure, explains the origins of his striking moniker, and describes the bloody skirmish that ended his life. Sidebars and fact boxes offer more information about both pirates and privateers and the perils of each chosen path."--From the publisher.